Cutis 2020
DOI: 10.12788/cutis.0087
|View full text |Cite
|
Sign up to set email alerts
|

An Unusual Skin Infection With Achromobacter xylosoxidans

Abstract: • Achromobacter xylosoxidans is an emerging pathogen primarily in the immunocompromised patient. • Achromobacter xylosoxidans can form biofilms on plastics treated with disinfectant solution, including medical products. • Strains of A xylosoxidans have shown multiantibiotic resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
1
0
1
Order By: Relevance
“…Инфекции дыхательных путей [65][66][67] Инфекции мочевыводящих путей, включая абсцессы почек и паранефральные абсцессы [68][69][70] Инфекции кровотока [71,72] Менингиты, абсцесс мозга [73,74] Абсцессы печени [5] Панкреатиты [75] Раневые инфекции, поражения кожи и подкожной клетчатки [75][76][77] Девайсассоциированные инфекции [78] Эндокардиты [79][80][81] Медиастиниты [4] Поражения ЛОРорганов (синуситы, отиты) [82,83] Поражения органа зрения (эндофтальмиты, кератиты) [84,85] Перитониты, абсцессы брюшной полости и забрюшин ного пространства [86,87] Остеомиелит…”
Section: патология ссылкаunclassified
“…Инфекции дыхательных путей [65][66][67] Инфекции мочевыводящих путей, включая абсцессы почек и паранефральные абсцессы [68][69][70] Инфекции кровотока [71,72] Менингиты, абсцесс мозга [73,74] Абсцессы печени [5] Панкреатиты [75] Раневые инфекции, поражения кожи и подкожной клетчатки [75][76][77] Девайсассоциированные инфекции [78] Эндокардиты [79][80][81] Медиастиниты [4] Поражения ЛОРорганов (синуситы, отиты) [82,83] Поражения органа зрения (эндофтальмиты, кератиты) [84,85] Перитониты, абсцессы брюшной полости и забрюшин ного пространства [86,87] Остеомиелит…”
Section: патология ссылкаunclassified
“…Achromobacter xylosoxidans is an emerging, multidrug-resistant pathogen involved in lung and soft tissue skin infection. It is common in nature and mainly found in water just like P. aeruginosa [8]. To date, there are no recognized co-infections due to P. aeruginosa and A. xylosoxidans in skin and skin appendages.…”
Section: Introductionmentioning
confidence: 99%
“…A large scale biocontamination monitoring found that 10% of the total samples tested were positive for A. xylosoxidans contamination, where the prevalence was stable throughout the investigation time [2]. These bacteria are facultative aerobes, thus their survivability in both aerobic and anaerobic conditions [4].…”
Section: Introductionmentioning
confidence: 99%